Identification of peroxisomal targeting signals located at the carboxy terminus of four peroxisomal proteins (The Rockefeller University Press, 1988)
As part of an effort to understand how proteins are imported into the peroxisome, we have sought to identify the peroxisomal targeting signals in four unrelated peroxisomal proteins: human catalase, rat hydratase:dehydrogenase, pig D-amino acid oxidase, and rat acyl-CoA oxidase. Using gene fusion experiments, we have identified a region of each protein that can direct heterologous proteins to peroxisomes. In each case, the peroxisomal targeting signal is contained at or near the carboxy terminus of the protein. For catalase, the peroxisomal targeting signal is located within the COOH-terminal 27 amino acids of the protein. For hydratase:dehydrogenase, D-amino acid oxidase, and acyl-CoA oxidase, the targeting signals are located within the carboxy- terminal 15, 14, and 15 amino acids, respectively. A tripeptide of the sequence Ser-Lys/His-Leu is present in each of these targeting signals as well as in the peroxisomal targeting signal identified in firefly luciferase (Gould, S.J., G.-A. Keller, and S. Subramani. 1987. J. Cell Biol. 105:2923-2931). When the peroxisomal targeting signal of the hydratase:dehydrogenase is mutated so that the Ser-Lys-Leu tripeptide is converted to Ser-Asn-Leu, it can no longer direct proteins to peroxisomes. We suggest that this tripeptide is an essential element of at least one class of peroxisomal targeting signals.